2022
DOI: 10.34190/ejel.20.4.2203
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Study of EFL Teachers’ Perception toward E-learning Platforms during the Covid-19 Pandemic

Abstract: The study critically examines the features of three such e-learning platforms: Blackboard, Google Classroom, and Zoom. It provides an in-depth analysis of the digital learning podium's effectiveness in a pandemic like COVID-19. It synthesizes the strengths and limitations of the selected e-learning platforms for English language teaching. The study focuses on authentic e-learning platforms' potentials to encourage EFL teachers and learners to take the challenge of adapting to a transforming world that could en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results showed that the students supported e-learning due to its cost, flexibility, efficiency, and confidence. Khalil & Alharbi (2022) examined EFL teachers' views of e-learning platforms during Covid-19, especially Zoom, Blackboard, and Google Classroom. It is shown that Google Classroom is the most effective platform for EFL learning, then Blackboard and Zoom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the students supported e-learning due to its cost, flexibility, efficiency, and confidence. Khalil & Alharbi (2022) examined EFL teachers' views of e-learning platforms during Covid-19, especially Zoom, Blackboard, and Google Classroom. It is shown that Google Classroom is the most effective platform for EFL learning, then Blackboard and Zoom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The world of education is currently starting to be influenced by developments in information and communication technology. In this way, the use of information and communication technology in the world of education gives rise to new ideas in learning, resulting in a paradigm shift from previously being more passive which only relied on what was given by the teaching staff or still being conventional to being more active and centered on the participants (Alharbi & Khalil, 2022). The world of education is currently starting to be influenced by developments in information and communication technology.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in computer science technology in the areas of multimedia, web-based learning, digital technology and others are exciting to explore as they benefit academics, office employees and people working at home. (Alharbi & Khalil, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…1) Training and Practice, 2) Tutorial, 3) Simulation, 4) Computer-instructed learning. It is exciting to explore the opportunities arising from advances in multimedia, web learning, and other cutting-edge digital revolution technologies available in virtually all areas of life that offer potential advantages to people in the workplace, academia, and home (Alharbi & Khalil, 2022).…”
Section: Introductionmentioning
confidence: 99%